Testosterone, cortisol and anxiety in elite field hockey players - Aguilar, R.; Jimenez, M.; Alvero-Cruz, J. R. (Physiology & Behavior, 2013)
The aim of the present study was to assess the change in the levels of testosterone and cortisol after victory and defeat in male field hockey players during an important tournament. In the beginning of the game series, the players were ranked very closely to achieve (for the first time) the championship rising to The Honor Division-A, the highest status national category. The first game resulted in a 7-4 victory, the second game resulted in a 6-1 victory, and the third game resulted in a 1-2 defeat. As expected, there were changes in testosterone levels after the competition, dropping in the game which ended in defeat, and rising slightly in the two games which ended in victory; there were also changes in cortisol levels, rising in the game which ended in defeat, and showing no variations in the games which ended in victory; correlational analyses congruently showed that defeat led to rises in cortisol whereas victory led to rises in testosterone; anticipatory somatic anxiety was related to cortisol levels prior to games, and physical exertion during competition was related to the change in testosterone levels (suggesting an inhibitory effect) but not to the change in cortisol levels. Hence, this pattern of hormonal responses to a real-life dominance challenge complied with Mazur's (1985) [16] biosocial model of status and dominance motivation, by showing that testosterone and cortisol are linked to victory and defeat in a theoretically predictable fashion.